PENEMUAN (DETEKSI) ANTIBODI UNTUK ANTIGEN TUBERKULOSIS MENGGUNAKAN METODE IMUNOKROMATOGRAFI DI PENDERITA TUBERKULOSIS PARU - Kadek Mulyantari; Aryati .; M.Y. Probohoesodo (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2008)
The gold standard for TB still has some drawbacks, such as a long duration for culture examination and the rolated facilities are notalways available in all laboratories. One of methods in diagnosing tuberculosis infection is by immunochromatography (ICT). MYCOTECTB xp (recombinant) is one of serologic tests using immunochromatography principle. MYCOTEC TB xp uses recombinant antigens 38kDa, 16 kDa, 6 kDa and Early Secreted Antigen Target (ESAT-6). This method is expected so far diagnose TB in a short time and has ahigh accuracy. Evaluating the immunochromatography method in detecting antibody by tuberculosis antigen in lung TB patients as willthose with nonTB lung disease (lung tumor, bronchial asthma, pneumonia, chronic obstructive lungdisease). Serum samples of 30 TBpatients in BP4/Karang Tembok Hospital Surabaya and 30 non TB patients in the Dr. Soetomo Hospital Surabaya. Detection of antibodyto tuberculosis antigen was done with MYCOTEC TB xp. In this study found is prond 30 TB patients using MYCOTEC TB xp was positivein 23 samples and negative in 7 samples. From the 30 nonTB patients MYCOTEC TB xp was positive in 4 samples and negative in 26samples. It can be uncloaded so far that the diagnostic sensitivity of MYCOTEC TB xp was 76.7% (23/30) and diagnostic specificity was86.7% (26/30). MYCOTEC TB xp has an intermediate diagnostic sensitivity of 76.7% and a high diagnostic specificity of 86.7%.